Heparanase of murine effector lymphocytes and neutrophils is not required for their diapedesis into sites of inflammation. Issue 5 (29th January 2015) - Stoler‐Barak, Liat; Petrovich, Ekaterina; Aychek, Tegest; Gurevich, Irina; Tal, Orna; Hatzav, Miki; Ilan, Neta; Feigelson, Sara W.; Shakhar, Guy; Vlodavsky, Israel; Alon, Ronen
ABSTRACT: Heparanase, the exclusive mammalian heparan sulfate‐degrading enzyme, has been suggested to be utilized by leukocytes to penetrate through the dense basement membranes surrounding blood venules. Despite its established role in tumor cell invasion, heparanase function in leukocyte extravasation has never been demonstrated. We found that TH 1/TC 1‐type effector T cells are highly enriched for this enzyme, with a 3.6‐fold higher heparanase mRNA expression compared with naive lymphocytes. Using adoptive transfer of wild‐type and heparanase‐deficient effector T cells into inflamed mice, we show that T‐cell heparanase was not required for extravasation inside inflamed lymph nodes or skin. Leukocyte extravasation through acute inflamed skin vessels was also heparanase independent. Furthermore, neutrophils emigrated to the inflamed peritoneal cavity independently of heparanase expression on either the leukocytes or on the endothelial and mesothelial barriers, and overexpression of the enzyme on neutrophils did not facilitate their emigration. However, heparanase absence significantly reduced monocyte emigration into the inflamed peritoneal cavity. These results collectively suggest that neither leukocyte nor endothelial heparanase is required for T‐cell and neutrophil extravasation through inflamed vascular barriers, whereas this enzyme is required for optimal monocyte recruitment to inflamed peritoneum.—Stoler‐Barak, L., Petrovich, E., Aychek, T., Gurevich, I., Tal, O., Hatzav, M., Ilan, N., Feigelson, S. W., Shakhar, G., Vlodavsky, I., Alon, R. Heparanase of murine effector lymphocytes and neutrophils is not required for their diapedesis into sites of inflammation. FASEB J. 29, 2010‐2021 (2015). www.fasebj.org